Pengaruh Promosi dan Kualitas Produk Terhadap Keputusan Pembelian Produk Keripik Sokressh Malang - Novita Ardhianti Wahyuningtyas; Tundung Subali Patma (Jurnal Bisnis Inovatif dan Digital, 2025)
Currently the growth of culinary is increasingly competitive, Every small medium enterprise must pay attention to the strategies to retain consumers. Promotion and product quality can influence the consumer's purchasing decisions. The objective of this research was to analyze the effect of promotion and product quality on purchasing decisions of Sokressh Malang chips. This research was a quantitative research with variables of promotion and product quality as independent variables while purchasing decisions as the dependent variable. The data collection was conducted by distributing questionnaires from 100 respondents who were instagram followers of Sokressh Malang chips. The respondents were selected through the purposive sampling method. The methods of data analysis used multiple regression analysis and hypothesis testing. The conclusion of this study is that promotion and product quality partially and simultaneously have a positive and significant effect on purchasing decisions for Sokressh Malang chips. It is expected that Sokressh Malang chips can make more attractive promotion, and innovattions on products by improving the product quality, in order that the consumers will be interested to buy Sokressh Malang chips.